Intervenções do professor de educação especial diante de síndromes raras do desenvolvimento - Machado, Andressa (2024)
This Master's research was developed within the scope of the Postgraduate Program in Education at the Federal University of Santa Maria (UFSM) and is part of the research line “Special Education, Inclusion and Difference”. This study is part of the theme of school inclusion, more specifically regarding the role of Special Education teachers in the face of the challenges of rare syndromes, the schooling process of these individuals and possible educational interventions. Thus, the study has the general objective of understanding the pedagogical strategies and interventions adopted by Special Education teachers in the face of the manifestation, in childhood, of rare developmental syndromes. The approach in relation to the methodology revolves around an analysis in favor of qualitative research, which is guided by the application of a questionnaire with teachers from resource rooms in public schools in Santa Maria. The interview is structured around the following axes: identification data, perspective from the training of Special Education teachers, practical experience, resources and support, collaboration, challenges in dealing with these cases and continuing education. We can mention that the above objective was partially answered, considering that the participants who answered the questionnaire mentioned that there are no specific strategies, the guidelines are individual for each case, the strategies adopted were not mentioned in their entirety during the research. Although Special Education teachers have a technical base that enables them to carry out pedagogical interventions, the complexity of rare developmental syndromes requires a commitment to continuous training, in addition to this, renewal and investment are needed, reflecting on interdisciplinary collaboration and a flexible and adaptive approach. Only then will they be able to adequately meet the needs of each student, promoting true and effective inclusion.